1963
DOI: 10.1073/pnas.50.1.68
|View full text |Cite
|
Sign up to set email alerts
|

Physical and Chemical Properties of Rna From the Bacterial Virus R17

Abstract: The anti-p-azobenzenearsonic acid antibody will be referred to subsequently in this paper as arsonic antibody. Similarly, the anti-p-azophenyltrimethylammonium antibody is abbreviated to ammonium antibody. ' Zaki, A., and H. Fahim, J. Chem. Soc., 270 (1942). The radioactive compound was prepared by New England Nuclear Corp., Boston, Mass., on the basis of the methods developed in this laboratory.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
0

Year Published

1965
1965
1979
1979

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(15 citation statements)
references
References 12 publications
1
14
0
Order By: Relevance
“…1 for RI. The OD (260 m,u) was 0.832; the patterns were photographed at 8, 16, and 24 min after reaching speed (52,640 rev/min); the temperature was 20.0 C; and r/2 was 0.06. degradation products (22). In contrast, RI was a completely heterogeneous population of molecules, as might be expected from the pattern of RI obtained by sucrose density gradient centrifugation (11).…”
Section: Resultsmentioning
confidence: 77%
See 2 more Smart Citations
“…1 for RI. The OD (260 m,u) was 0.832; the patterns were photographed at 8, 16, and 24 min after reaching speed (52,640 rev/min); the temperature was 20.0 C; and r/2 was 0.06. degradation products (22). In contrast, RI was a completely heterogeneous population of molecules, as might be expected from the pattern of RI obtained by sucrose density gradient centrifugation (11).…”
Section: Resultsmentioning
confidence: 77%
“…Indeed, the value of / which yields a molecular weight closest to Mw (theoretical) = 2.9 X 106 is again 2.5 x 106. Mitra et al (22) pointed out that the value of /3 should not be greater than 2.5 X 106 for R17 RNA and Eigner and Doty (5) showed that (i) / = 2.5 X 106 for native DNA, and (ii) / = 2.3 X 101 for denatured DNA (although the values varied between 1.6 X 106 and 2.6 x 106 in this case). Furthermore, /3 has been shown to have the value of 2.5 X 106 for many synthetic polymers (8).…”
Section: Discussionmentioning
confidence: 80%
See 1 more Smart Citation
“…For the small RNA-containing bacteriophages, whose RNA has a molecular weight of 1.1 X 106, both hydrodynamic and spectroscopic data show that 60-80% of the RNA exists in the form of short base-paired loops (1)(2)(3)(4)(5). Recently, sequence analysis has also shown that the bacteriophage RNA contains many internal regions which are self-complementary and which could produce hairpin loops by base pairing (6,7).…”
mentioning
confidence: 99%
“…I n order to make either interpretation possible, MS2 RNA must remain, a t least partially, double-stranded during the infection. Since 700/, of the MS2 RNA is doublestranded [16], it seems unlikely that a break in one of the double-strand regions of the RNA makes the RNA fall apart. The possibility that the RNA is repaired cannot be excluded, especially in the light of the recent report of an E. coli RNA ligase [17].…”
Section: 1~0~ [S]mentioning
confidence: 99%